Efficacy and Safety of Multiband Mucosectomy Versus Cap-assisted Endoscopic Resection For Early Esophageal Cancer and Precancerous Lesions: A Systematic Review and Meta-Analysis. Issue 5 (October 2019) - Dan, Xiang; Lv, Xiu-He; San, Zhi-Jie; Geng, Sang; Wang, Yan-Qiang; Li, Shao-Hua; Xie, Hua-Hong
Abstract : Background: The effectiveness of multiband mucosectomy (MBM) for early esophageal cancer and precancerous lesions is still in uncertainty. We aimed to evaluate the efficacy and safety of this procedure and to compare it with cap-assisted endoscopic resection (EMR-cap). Methods: A systematic search of both English and Chinese databases was performed from inception to April 30, 2019. Complete resection rate, local recurrence rate, and procedure time were considered the primary outcome measures. Prevalence of complications was considered the secondary outcome measure. All data analyses were performed using Review Manager Software. Results: Two randomized controlled trials (RCTs) and 3 non-RCTs were included in the final meta-analysis. When compared with the EMR-cap technique, MBM had a similar complete resection rate [odds ratio (OR)=2.09, 95% confidence interval (CI): 0.78-5.60, P =0.14], a similar local recurrence rate (OR=0.50, 95% CI: 0.09-2.67, P =0.42), a shorter resection time (mean difference: −9.08, 95% CI: −13.86 to −4.30, P =0.0002), a shorter procedure time (mean difference: −13.36, 95% CI: −17.85 to −8.86, P <0.00001), a lower bleeding rate (OR=0.45, 95% CI: 0.24-0.83, P =0.01), a similar perforation rate (OR=0.55, 95% CI: 0.15-2.06, P =0.37), and a similar stricture rate (OR=0.77, 95% CI: 0.10-5.84, P =0.80). The results of non-RCTs were consistent with those of RCTs. Conclusions: MBM is similar to EMR-cap in terms of efficacy and safety for endoscopic resection of early cancer and precancerous lesions of the esophagus. However, MBM is less time-consuming.